2018
DOI: 10.1016/j.rmed.2018.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction is associated with impaired lung function in two independent community cohorts

Abstract: Our findings suggest that even individuals with sub-clinical impairments of lung function in the community have concomitant endothelial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…These findings indicate that endothelial function contributes to CBF regulation. On the other hand, endothelial function is impaired by respiratory dysfunction (63). Moreover, previous study (9) demonstrated that endothelial dysfunction of the cerebral vasculature is related to increase in oxidative stress.…”
Section: Reactive Oxygen Species and Endothelial Functionmentioning
confidence: 98%
“…These findings indicate that endothelial function contributes to CBF regulation. On the other hand, endothelial function is impaired by respiratory dysfunction (63). Moreover, previous study (9) demonstrated that endothelial dysfunction of the cerebral vasculature is related to increase in oxidative stress.…”
Section: Reactive Oxygen Species and Endothelial Functionmentioning
confidence: 98%
“…Moreover, it is important to explore factors common to lung function and atherosclerosis to prevent CVD. dysfunction, and cIMT [52][53][54] . Therefore, although arterial stiffness and endothelial dysfunction may be confounding factors for the association between lung function and cIMT, we could not consider them because we did not collect information on them.…”
Section: Advance Publication Journal Of Atherosclerosis and Thrombosismentioning
confidence: 99%